ENDOTHELIAL NITRIC OXIDE CONCENTRATIONS IN THE SALIVA OF JIU-JITSU ATHLETES - Agricola,Nestor Persio Alvim (2020)
ABSTRACT Introduction This article discusses the production of nitric oxide under the influence of sport-specific physical training, measured by the salivary nitrite of Jiu-Jitsu athletes. Objectives To verify the potential of the sport to produce optimal levels of nitric oxide stimulated by exertion, and to quantify training-related nitric oxide concentrations. Method The study participants were 14 volunteer athletes from the Tatame project (extension project), who were monitored for nine months in their training routine, providing samples of unstimulated saliva. Samples were collected each month, in three periods of the day: in the morning upon waking, immediately before training, and immediately after training. Salivary nitrite was quantified by the colorimetric Griess assay. Training heart rates were also monitored in order to establish training intensity. Results Mean monthly salivary nitrite levels showed a significant correlation with mean monthly heart rates, suggesting that salivary nitrite responds to training. However, salivary nitrite concentrations measured immediately after training were always lower than in the pre-training period. Conclusion The post-training reduction in concentrations was due to the nature of the sport studied, since because it involves a fight, the intense sympathetic stimulation inhibited salivary gland activity and irrigation, preventing salivary nitrite from producing an increase in circulating nitric oxide. Level of evidence IV; Case series.